PROSPECTS OF MANUFACTURE OF PISTON RINGS INTERNAL COMBUSTION ENGINES OF POWDER MATERIALS ON THE BASE OF IRON - B. M. Musaibov; M. U. Ahmedpashaev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Development and production of piston rings made of sintered materials on the basis of iron powder metallurgy is an innovative way. In the application of this technology reduces the consumption of material and costs for the production of piston rings 30-40% in comparison with the traditional methods of their manufacture